Renewable energy transformation using solar panels in the Red Tilapia Intensive System community - Shoffin Nahwa Utama; Wahyu Hariyanto; Nurizal Dwi Priandani (University of Merdeka Malang, 2024)
The transition to renewable energy is a strategic response to the global energy crisis and climate change. A community service project was conducted to promote energy independence for the Red Tilapia Intensive System (REDTIS) community by installing solar panels. Utilizing the Asset-Based Community Development (ABCD) method, the initiative involved installing two solar panels with a total capacity of 200 WP, a 100 AH battery, a 30 A solar charge controller, and a 500 Watt inverter to power a 100-Watt aerator. The project began with community asset identification, renewable energy analysis, system design, installation, and performance monitoring. The solar panel system generated an average of 1 kWh daily, covering approximately 41.3 percent of the aerator's 2.4 kWh daily energy requirement. This reduced reliance on conventional energy, lowering electricity costs and carbon emissions. While the solar panels did not fully meet the aerator's energy needs, the initiative demonstrated significant potential for scalability. Enhancing energy production, storage, and management is expected to achieve complete energy independence. This project serves as a replicable model for other communities seeking sustainable energy solutions.